Cryptic biodiversity of freshwater fish species in Bangladesh - Mahmudul Hasan; Chiaki Kambayashi; Zahid Hasan Anik; Md. Saiful Islam (PLoS ONE, 2025)
Unrecognized cryptic species impede conservation planning and biodiversity assessments. DNA barcoding has tremendously expanded the number of novel and cryptic species in biological science. Despite few sporadic studies, the exact number of freshwater species found in Bangladesh is not known. To assess this biodiversity, we sequenced the COI gene of 124 freshwater specimens, which were gathered from various localities around Bangladesh. Seven cryptic species hidden among the currently studied specimens were identified based on the findings of phylogenetic and species delimitation analyses. The preliminary assessment also encompassed a restricted morphological examination of these cryptic taxa. The appearance of cryptic species, some of them possibly endemic, has been hypothesized. This raises concerns regarding the true diversity and evolutionary history of freshwater species in Bangladesh, which are significantly underrepresented in the current systematic frameworks that do not account for DNA data. Our current study provides baseline data that might aid local ichthyologists in their quest to identify additional new species by combining several variables (morphology and ecology). Further research is warranted to protect the priceless freshwater species in Bangladesh.